2016
DOI: 10.11648/j.wros.20160505.11
|View full text |Cite
|
Sign up to set email alerts
|

Farmer’s Perception on Soil Erosion and Land Degradation Problems and Management Practices in the Beressa Watershed of Ethiopia

Abstract: In Ethiopia erosion and land degradation on the livelihood resource had become a key issue, resulted for food insecurity and difficult to break through the poverty gap using subsistence farming. Previously implemented soil and water conservation practice were not halted the threat, because it was mass mobilization without detailed study of real situation and without convicting farmers. Over sighting the past experience, community based watershed management practice was recommended as a possible option against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Regarding signs with which it can be identified, they rightly mentioned visible erosion features such as sheet, rills, gullies, and landslides. This is in agreement with [54] who reported the same results for Beressa watershed Ethiopia. [11], also reported 98.4% of the surveyed farmers recognized that soil erosion was a problem in their own farm.…”
Section: Farmers' Perception On Soil Erosion and Physical Soil And Wasupporting
confidence: 93%
“…Regarding signs with which it can be identified, they rightly mentioned visible erosion features such as sheet, rills, gullies, and landslides. This is in agreement with [54] who reported the same results for Beressa watershed Ethiopia. [11], also reported 98.4% of the surveyed farmers recognized that soil erosion was a problem in their own farm.…”
Section: Farmers' Perception On Soil Erosion and Physical Soil And Wasupporting
confidence: 93%
“…Consistent with the present erosion indicators, Bukari et al [ 67 ] have reported that farmers perceived sheet erosion (68%) and gully erosion (60%) as the most frequently noted indicators of erosion severity. Several other researchers elsewhere have reported in Africa similar soil degradation (erosion) indicators even though there are some variability on the rank of their importance spatially and temporally (e.g., [ 74 76 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of LCLUC on climate, especially precipitation, cannot be ignored. At present, many studies have been done on the impact of LCLUC [2,4], including temperature, circulation, carbon emissions, runoff-sediment [5], and other aspects [6][7][8]. However, there have also been studies on the negative environmental effects of anthropogenic LCLUC to improve crop production [9].…”
Section: Introductionmentioning
confidence: 99%